Parametric study of heat transfer characteristics of enhanced surfaces in a spray cooling system: An experimental investigation. (25th January 2021) - Salman, Azzam S.; Abdulrazzaq, Nabeel M.; Tikadar, Amitav; Oudah, Saad K.; Khan, Jamil A.
Highlights: Surface (M3) has better heat transfer characteristics than a surface modified with only straight grooves by up to 34%. The maximum heat transfer enhancement ratio of all surfaces occurs at a surface temperature difference of 15 K. Spray cooling heat transfer characteristics depend on the surface structure more than the wetted surface area. Abstract: In this paper, a series of experiments were conducted to investigate the influences of nozzle-to-surface distance, coolant volumetric flow rate, and temperature difference between the target surface and coolant inlet temperatures, on the heat transfer characteristics of enhanced surfaces in a spray cooling system. Three different structures of macro circular and radial grooves, having depth and width of 500 × 500 μm, respectively, were machined directly on the top of a 15 mm copper surface. Surfaces were enhanced with four circular grooves (M1), a combination of four circular and four radial grooves (M2), and a combination of four circular and eight radial grooves (M3), to increase the wetted surface area and disturb both thermal and hydraulic boundary layers. These surfaces were tested in a closed-loop spray cooling system, utilizing deionized (DI) water as a coolant, at nozzle-to-surface distances, temperature differences, and volumetric flow rates ranging between 8–12 mm, 5–75 K, and 115–180 mL/min, respectively. During all experiments, both chamber pressure and coolant inlet temperature were maintained approximately constant at atmospheric pressure and 295 K, respectively. The results illustrate that radial grooves and surface structures play a more important role than spray coverage area and surface wetted area in the thermal performance of a surface because radial grooves increase the fluid velocity and decrease the fluid film thickness over the target surface and eventually reduce the convective thermal resistance. Furthermore, it was observed that M3 has the highest heat transfer enhancement ratio, followed by M2 and M1, at all experimental conditions, due to the reduction in the convective thermal resistance and the slight increase in the wetted surface area. The maximum average heat transfer enhancement ratios compared to a plain surface at a temperature difference range of 15–75 K for enhanced surfaces M3, M2, and M1 are ∼ 67, ∼ 31, a n d ∼ 23 % at a volumetric flow rate and nozzle-to-surface distance of 180 mL/min and 10 mm, respectively. Additionally, the heat transfer characteristics of enhanced surface M3 were compared based on the wetted surface area at the same operating conditions with a surface enhanced with only straight grooves, having a depth and width of 500 × 200 μ m . The comparison showed that, at a volumetric flux of 12.73 L/(m 2 .s), M3 has better thermal characteristics than the surface modified with straight grooves by 34%.